GESTÃO ECONÔMICO FINANCEIRA NOS HOSPITAIS FILANTRÓPICOS. ORGANIZAÇÃO E FINANCIAMENTO: O Caso da Associação dos Amigos do Hospital Mário Penna - Castro, Roberto Maximo (2002)
The objective study to argue a form of support to the pertaining hospitals pertaining to the philanthropy entities, on the basis of a System of Management that contemplates the development of enterprise strategies, front to the consequences of verified mutations, with entrance of resources of investments destined to the increase of the complexity of the medical assistance - hospital. With the aid of the study of the case of a typical institution, that search its self-sustain. Association of the Friends of the Hospital Mário Penna -, through the strategic evaluation of the business it was possible to investigate the adequacy of the methodology. analysis of standard of the management, and to arrive it a statement on a preliminary proposal of strategies of modernization of the management of a philanthropy hospital Evaluated the critical aspects of analysis of the management standard in periods of inversions and its consequences in the yield of the operations. The study it allowed it was identified to which the strategies already developed or in development for hospitals and its respective unfolding. In the first part the internal and external examination of the institution and the determinative factors of the competitiveness been investigated defining its forces and weaknesses and identifying to its threats and chances for redefinition of the mission of the institution. In the second they had been investigated the internal and external examination of the business searching to identify to the internal critical factors and evaluation of its position to reach the competitive advantage, as well as identifying the external factors that contribute for the attractiveness of the industry. In the third part a business plan/action for the high direction of the institution was presented having aimed at to constitute the bases to guarantee the sustentabilidade and the perprtual for theinstitution. Parallel to the present work, the development of the Study of the Hospital Sector Philanthropy in Brazil ( Bndes/ensp/fiocruz-2002 Resesrch) allowed to identify the positioning of the hospitals of the AAHMP in the context of the system of health adopted for the Country. In this particular one, the importance of this sector for the public politics of hospital attention in Brazil. In function of this one becomes basic to enhance that the management of a philanthropy company must be enterprising and creative of values for the society. Implications of this position for the system of financial economic information must be dealt with the clarity of the criteria of the system of economic management. First, the model of organization of the system of heath is considered adopted in Brazil, where the creation of value of the activities of the philanthropy organization of health and the economic criteria of measure of the results are examined and waited. Finally, the impact of the enterprising position of the process of management and in the system of information of a philanthropy organization is verified in view of, on the other hand, the legal relationship of the organization with the superior authority and for another one the necessities of management of the creation of value for the society. It is the counterpart of the fiscal resignation. Thus, the model of management of the philanthropy, rendering organizations of health services, must have as line of direction the balance enters the attainment of positive result and the rendering of services of social matrix